Taking stock: a review of the known parasites of the sleepy lizard, Tiliqua rugosa (Gray, 1825), a common lizard endemic to Australia. Issue 2 (3rd July 2019) - Norval, Gerrut; Ross, Kirstin E.; Sharrad, Robert D.; Gardner, Michael G.
ABSTRACT: Parasitism is a very common life strategy and although it results in harm to the host, it plays a vital ecological role in host population and community dynamics. The sleepy lizard, Tiliqua rugosa, is one of the best studied lizard species in Australia, to a large extent due to studies involving ticks that infest these lizards. In spite of this, little is known about most of the parasites that are known to infect sleepy lizards. The purpose of this review is to provide a synopsis of the species that have been reported as parasites of T. rugosa as a foundation for future studies.